Sebaran Potensi Mata Air dan Kearifan Lokal Masyarakat dalam Rangka Upaya Konservasi Sumber Daya Air di Kecamatan Akabiluru Kabupaten Lima Puluh Kota - Maulana, Fhiqram; Ideal, Helfia (Lembaga Yasin AlSys, 2025)
The need for water is very important for life, both agriculture, industry and daily life, causing people to have to look for existing sources to meet their water needs. This study aims to analyze the location of existing water sources and determine the feasibility of water sources by conducting laboratory tests, after that to maintain water sources, community cooperation is needed, one of which is the form of local wisdom in maintaining water sources in Akabiluru District. The method used is descriptive quantitative. The results of the study stated that there are 22 springs spread across Akabiluru District, laboratory tests were carried out with samples of 3 springs, namely Luak Napa, Luak Canduang, Pancuran Duo. The three springs showed good physical water quality, colorless, tasteless and odorless. Meanwhile, the results of the chemical parameter laboratory tests, the water pH is normal except in Pancuran Duo with a pH of 6.1 and the manganese content does not exceed the standard, the mineral content such as calcium, potassium, and magnesium does not exceed the maximum levels allowed according to the drinking water quality standards, and for the microbiological parameters, the coliform content is quite high in the three samples, namely >.2400 MON / 100 ml and 43 MPN / 100 ml. Local wisdom in Akabiluru District in maintaining existing springs is still carried out in several villages such as prohibiting taking water at noon, cleaning springs, and making several water sources sacred springs.